Sacred space in the modern city the fractured pasts of Meiji shrine, 1912-1958 - Imaizumi, Yoshiko (Boston : Brill, 2013)
Sacred Space in the Modern City offers new and original perspectives on a number of controversial issues and important questions concerning Japanese pre- and post-war ideology and identity. The author uses Meiji shrine as a lens with which to investigate the nature of the society that created, experienced and reproduced this site.
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: Meiji Jingū (Tokyo, Japan); Architecture and society -- Japan -- Tokyo; Nationalism and architecture -- Japan -- Tokyo; Nationalism -- Religious aspects -- Shinto; Tokyo (Japan) -- Buildings, structures, etc; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Comparative Religion; Electronic books